Small molecule mediated inhibition of RORγ‐dependent gene expression and autoimmune disease pathology in vivo. Issue 4 (26th January 2016) - Banerjee, Daliya; Zhao, Linlin; Wu, Lan; Palanichamy, Arumugam; Ergun, Ayla; Peng, Liaomin; Quigley, Catherine; Hamann, Stefan; Dunstan, Robert; Cullen, Patrick; Allaire, Norm; Guertin, Kevin; et al.
Summary: Retinoic acid receptor‐related orphan nuclear receptor γ (ROR γ ) orchestrates a pro‐inflammatory gene expression programme in multiple lymphocyte lineages including T helper type 17 (Th17) cells, γδ T cells, innate lymphoid cells and lymphoid tissue inducer cells. There is compelling evidence that ROR γ ‐expressing cells are relevant targets for therapeutic intervention in the treatment of autoimmune and inflammatory diseases. Unlike Th17 cells, where ROR γ expression is induced under specific pro‐inflammatory conditions, γδ T cells and other innate‐like immune cells express ROR γ in the steady state. Small molecule mediated disruption of ROR γ function in cells with pre‐existing ROR γ transcriptional complexes represents a significant and challenging pharmacological hurdle. We present data demonstrating that a novel, selective and potent small molecule ROR γ inhibitor can block the ROR γ ‐dependent gene expression programme in both Th17 cells and ROR γ ‐expressing γδ T cells as well as a disease‐relevant subset of human ROR γ ‐expressing memory T cells. Importantly, systemic administration of this inhibitor in vivo limits pathology in an innate lymphocyte‐driven mouse model of psoriasis.